PEMAHAMAN DAN PENGHAYATAN MAHASISWA STKIP WIDYA YUWANA TERHADAP VISI, MISI DAN TUJUAN STKIP WIDYA YUWANA - Silviana Elisken; Ola Rongan Wilhemus (Lembaga Penelitian STKIP Widya Yuwana, 2019)
College of Teacher Training and Education (STKIP) Widya Yuwana Madiun is an educational institution that forms Catholic Catechists and Teachers. College students are educated and nurtured to become candidates for catechists and religion teachers in accordance with the Vision and Mission of